EFEKTIVITAS MEDIA PERTUMBUHAN KHAMIR KOMERSIAL (Saccharomyces cerevisiae) UNTUK FERMENTASI BIOETANOL DARI ECENG GONDOK (Eichhornia crassipes): Effectiveness of Growth Media Commercial Yeast (Saccharomyces cerevisiae) For Bioethanol Fermentation From Water Hyacinth (Eicchornia crassipes) - Febriyanti, Anugerah Eka; Sari, Cut Nanda; Adisyahputra, Adisyahputra (LPPM Universitas Negeri Jakarta, 2016)
This study aims to find growth medium commercial yeast (S.cerevisiae) and determine the optimum composition of bioethanol fermentation. This research was conducted at the Laboratory of Bioprocess PPPTMGB â€œLEMIGASâ€ along May to September 2015. The method used is experiment using a completely randomized design consisting of two treatment. The first treatment is an alternative growth media utilization, namely, tofu liquid waste, coconut water and a mixture of both. The second treatment is the composition of the fermentation with sugar content of 100 ml, 150 ml and 200 ml with the addition of 10 ml starter in each experiment. Data of commercial yeast cell growth (S.cerevisiae) on alternative growth media were analyzed by Anova one way. The results showed that there was an interaction of commercial yeast cell growth (S.cerevisiae) on alternative growth media. Post-hoc test showed the alternative media that consists of a mixture of tofu liquid waste and coconut water produce the highest commercial yeast cell growth at 25,8 x107 with a 7.62 log value (cells/ml). The most optimum of bioethanol produced in the fermentation process is on sugar 100 ml by the addition of 10 ml starter acquire as much as 45 ml of ethanol content.